1990
DOI: 10.1017/s0031182000061333
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and immunology of Necator americanus infection in a community in Papua New Guinea: humoral responses to excretory-secretory and cuticular collagen antigens

Abstract: SUMMARYBaseline data from an immuno-epidemiological study of hookworm infection in a rural village in Madang Province, Papua New Guinea are reported. Necator americanus was found to be the commonest helminth infection, with a prevalence of near 100% and intensity of 40 worms per host in adults. Enterobius vermicularis, Ascaris lumbricoides and Trichuris trichiura were also present, at prevalences of 53, 10 and 3% respectively; Ancylostoma duodenale was absent. The frequency distribution of N. americanus was hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
65
3

Year Published

1992
1992
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(71 citation statements)
references
References 28 publications
3
65
3
Order By: Relevance
“…Most hookworm L3 cast their outer sheaths on skin penetration (85), but some seem to retain the sheath; antibodies from people infected with N. americanus recognize surface antigens of ensheathed but not exsheathed L3 by immunofluorescence (112). Antibodies have been detected to L3 exsheathing fluid, prompting the suggestion that the cast sheath and associated antigens diverted the immune response away from the potentially vulnerable larval surface (69).…”
Section: Humoral Responsementioning
confidence: 99%
See 1 more Smart Citation
“…Most hookworm L3 cast their outer sheaths on skin penetration (85), but some seem to retain the sheath; antibodies from people infected with N. americanus recognize surface antigens of ensheathed but not exsheathed L3 by immunofluorescence (112). Antibodies have been detected to L3 exsheathing fluid, prompting the suggestion that the cast sheath and associated antigens diverted the immune response away from the potentially vulnerable larval surface (69).…”
Section: Humoral Responsementioning
confidence: 99%
“…Various methods have been used to identify these antibody responses, ranging from observation of immunoprecipitates around oral openings (102) to more detailed analyses of Ig subclasses against somatic and excretory/secretory (ES) products by enzyme-linked immunosorbent assay and Western blot analysis (79,80,112).…”
Section: Humoral Responsementioning
confidence: 99%
“…These included studies in Puerto Rico [10]; Australia [11]; Brazil [12,13]; Papua New Guinea [14]; India [15,16]; and Sri Lanka [17].…”
Section: Data Sources Relationship Between Prevalence Of Infection Anmentioning
confidence: 99%
“…The first approach was based on univariate statistical methods that essentially attempted to evaluate the effects of one antibody at a time to determine the role that each antibody played independently in regulating Wuchereria infection. This was accomplished via calculation of Pearson partial correlations between infection intensity and antibody variables within five age classes constructed to reflect the age structures of the two study communities (35), with tests for assessing heterogeneity in correlation coefficients between age classes carried out using methods described by Sokal and Rohlf (44). This was followed by an attempt to evaluate all the antibody effects simultaneously to determine their joint contributions to host regulation of worm intensity.…”
Section: Preparation Of Serummentioning
confidence: 99%
“…These studies unambiguously showed that W. bancrofti infection can induce strong antibody responses (4,29,32,42,47), but protective responses have not been conclusively identified yet. Recent theoretical analysis and evidence from other helminth infections (3,9,27,28,35,36) suggest that one reason for this situation in the study of filariasis could be the paucity of studies that have used an immunoepidemiological perspective to investigate the role of acquired immunity in influencing parasitic infection patterns in host communities in areas where the organism is endemic. In particular, this perspective, which attempts to link observed individual host immune responses to epidemiological patterns, has shown how observation of an increasingly negative correlation between the levels of an immune response and the intensities of infection with increasing host age could indicate a protective role for the response being examined (10,27,(48)(49)(50).…”
mentioning
confidence: 99%